Chaos control in vector-controlled induction motor drive - Ozer, A. Bedri; Akin, Erhan (Taylor & Francis Inc, 2008)
In this article, we present chaos control in a vector-controlled induction motor drive which has actually been implemented. A chaotic behavior appears when the stator flux components are estimated by means of a discrete implementation of an open-loop observer, based on the so-called voltage model. The voltage model has open integrations for both components of flux, which causes indefiniteness. Therefore, these chaotic behaviors may be eliminated by suitable control methods. The Pyragas control is a suitable method for chaotic systems, and this method is applied to the open integrations in the voltage model. In this article, we propose a method for successful elimination of the chaotic behavior and present experimental results to show the usefulness of this method.
Keywords: Pyragas control; chaos; vector control; induction motor